Physical Health Education Trends and Practices in Nepal: A Systematic Review - Prayag Raj Joshi (NPRC Journal of Multidisciplinary Research, 2026)
Background: There is an increasing need for physical health education in Nepal due to lifestyle changes, sedentary behavior, emergence of adolescent overweight and obesity, and noncommunicable diseases burden. In terms of schools, health and physical education has increasingly evolved beyond mere physical exercises and sports towards more holistic health education that includes health, fitness, nutrition, hygiene, mental wellbeing, safety, sexuality education, disease prevention, and healthy lifestyles. Methodology: This review presents policy documents, curricular resources, national surveys, and peer-reviewed publications on health education, physical education, physical activities, adolescent health, school health, nutrition, sedentary behavior, and their practice in Nepal. Peer reviewed studies conducted between 2021 to 2025 and studies with DOI identifier were considered priority. Relevant policy documents of the Curriculum Development Centre, Government of Nepal, and WHO have also been consulted. Findings: From the findings of this review, it can be seen that there is an evolving transition from sport-oriented physical education towards more integrated health and physical education approach. However, its implementation still varies. It can also be seen that adolescents, especially females, do not perform adequately physically active lifestyles, while screen-based lifestyle, urbanization, lack of recreational facilities, and academic pressure are some of the issues. Recent studies also point towards linkages among physical activity, dietary behaviors, obesity, internet use, school environment, parental involvement, and teachers' behavior. Conclusion: Although Nepal has achieved some progress towards recognition of health and physical education in the school curriculum, having curriculum included alone does not ensure good practice. More attention should be paid to activity-based learning, competent teachers, inclusiveness, school infrastructure, involvement of community, active transportation, monitoring and evidence-based interventions. Novelty: This review links curriculum development to empirical evidence on physical activity and school health practices to define the changing nature of physical health education in Nepal and suggest an integrative and contextual model for further practice.